CFD Investigation on the Influence of Roof Box Cargo Carrier Designs on Automobile Aerodynamics - Muhammad Amirul Hisamuddin,; Izuan Amin Ishak,; Mohammad Arafat,; Razlin Abd Rashid,; Ahmad Faiz Mohammad,; Nor Afzanizam Samiran,; Nor Atiqah Zolpakar, (International Journal of Integrated Engineering, 2025)
In recent years, roof carrier boxes have become increasingly popular among travelers and larger families for their added luggage capacity. While these boxes address insufficient boot space, they also increase the vehicle's frontal area, adversely affecting aerodynamics and increasing drag. Given that aerodynamics significantly impacts vehicle efficiency, the design of the roof box is critical in determining drag force. This study aims to minimize drag to enhance fuel economy by utilizing ANSYS, a commercial Computational Fluid Dynamics (CFD) software, to analyze the coefficient of drag (Cd) for a numerical car model equipped with three different roof box designs in three locations, as well as in the absence of a roof box. The simulation employs Reynolds Averaged Navier-Stokes (RANS) equations in combining with the k-? turbulence model. Concerning the stability of the vehicle influenced by the addition of the roof box, force coefficients, including drag and lift coefficients, were assessed. Results indicated that the drag and lift coefficients were highest at a speed of 25.5 m/s for all roof box configurations. The maximum Cd (0.4423) occurred with the XL model in the far backward position, while the highest Cl (0.4169) was observed with the Alpine model centrally positioned. Flow structure analysis highlighted vortex formation and wake turbulence at the vehicle's rear. Among the designs, the XL model in the central position was the most aerodynamically efficient, closely matching the base car's Cd and exhibiting the lowest Cl.